La estabilidad laboral reforzada de las mujeres embarazadas y en período de lactancia, frente al derecho a la igualdad laboral, Guaranda 2022. - Viscaíno Jiménez, Andrés Gabriel (2024)
The research work entitled: "The reinforced labor stability of pregnant and breastfeeding women, facing the right to labor equality, Guaranda 2022". It covers the subject of Labor Law, from the perspective of the rights of working women, who are pregnant or breastfeeding, because, at this time they are in a fragile situation that must be guaranteed by the State. The problem posed by this research is how to apply the right to labor equality to the reinforced labor stability of pregnant and breastfeeding women, starting from the fact that this special protection is practiced to facilitate the economic and social security means required by the workers to assume the expenses that all this entails; but, bearing in mind that the right to labor equality should also apply to the father, especially in cases where the woman is not working and depends on her partner, as well as the child that is about to be born. The research methodology uses a qualitative approach typical of the social sciences, especially in legal matters, which uses an interpretative analysis and the following methods: logical deductive and interpretative (textual, systematic, descriptive, historical). However, it was also necessary to use a quantitative approach to confirm the evidence that emerged during the research work, through validation by experts. Therefore, the approach used was quali-quantitative or mixed. The scope is descriptive in nature, the type of research is non-experimental because it was not necessary to manipulate the variables. The following methods were used: logical-inductive and interpretative to process information from documents such as legislation, doctrine, reports and jurisprudence. Document analysis was carried out using the document analysis guide. Therefore, this study is purely theoretical in nature. A survey directed to experts on this topic XVII was also conducted, for which the survey guide was used. Finally, the research work reached its main conclusions and recommendations through a process of synthesis. Key words: labor law, stability principle, worker's rights, parental co-responsibility.